Knowledge, perceptions and experiences of trachoma among Maasai in Tanzania: Implications for prevention and control. - Tara B Mtuy; Matthew J Burton; Upendo Mwingira; Jeremiah M Ngondi; Janet Seeley; Shelley Lees (Public Library of Science (PLoS), 2019)
Background The Alliance for the Global Elimination of Trachoma has set the target for eliminating trachoma as a public health problem by 2020. However, challenges remain, including socio-cultural issues. Districts in Northern Tanzania, predominantly inhabited by the Maasai ethnic group, remain endemic for trachoma. We explored socio-cultural factors that may impact the elimination of trachoma. Methods/findings This study was nested within a larger ethnographic study of trachoma among Maasai in Northern Tanzania. We used stratified random sampling and semi-structured interviews to examine knowledge and understanding. Interviews were conducted and recorded in Maa, by a native Maa speaking trained interviewer. Transcripts were translated into English. A framework method for a content analysis was used. There was awareness of trachoma and basic symptoms. Yet understanding of etiology and prevention was poor. Trachoma was attributed to pollen, dust, and smoke. Water was recognized as beneficial, but seen as treatment and not prevention. Traditional medicines were most often used for treating conjunctival inflammation, with the most common being a rough leaf used to scratch the inside of the eyelid until it bleeds. Knowledge of mass drug administration (MDA) was inconsistent, although many thought it helped the community, but it was perceived as only for children and the sick. Many participants reported not taking azithromycin and some had no recollection of MDA six months earlier. There was little connection between childhood infection, trichiasis and related blindness. Trichiasis was often seen as a problem of old women, and treated locally by epilation. Conclusion/significance Understanding indigenous knowledge may help guide control programs, tailor them to local contexts, address local beliefs and dispel misunderstandings. There is an essential need to understand the social, cultural and political context of the target community to deliver effective programs. Despite limited knowledge, the community recognized trachoma as a public health problem. Results have implications for disease control programs in other marginalized communities.